2001
DOI: 10.1073/pnas.061615598
|View full text |Cite|
|
Sign up to set email alerts
|

Heparin and cancer revisited: Mechanistic connections involving platelets, P-selectin, carcinoma mucins, and tumor metastasis

Abstract: Independent studies indicate that expression of sialylated fucosylated mucins by human carcinomas portends a poor prognosis because of enhanced metastatic spread of tumor cells, that carcinoma metastasis in mice is facilitated by formation of tumor cell complexes with blood platelets, and that metastasis can be attenuated by a background of P-selectin deficiency or by treatment with heparin. The effects of heparin are not primarily due to its anticoagulant action. Other explanations have been suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
650
2
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 623 publications
(694 citation statements)
references
References 49 publications
(64 reference statements)
27
650
2
9
Order By: Relevance
“…45 A major reason for heparin's chemoprotective effect may be through blocking of platelets that cloak circulating metastatic cancer cells by interfering with selectin-mediated interaction between platelets and neonatal mucin carbohydrates expressed by the cancer cells. 46 Wound Healing and Repair Processes. Many of the pathophysiological processes assisting the growth and spread of cancers are physiological processes, considered in a positive light in wound healing.…”
Section: Glycosaminoglycans In Cellular Communicationmentioning
confidence: 99%
“…45 A major reason for heparin's chemoprotective effect may be through blocking of platelets that cloak circulating metastatic cancer cells by interfering with selectin-mediated interaction between platelets and neonatal mucin carbohydrates expressed by the cancer cells. 46 Wound Healing and Repair Processes. Many of the pathophysiological processes assisting the growth and spread of cancers are physiological processes, considered in a positive light in wound healing.…”
Section: Glycosaminoglycans In Cellular Communicationmentioning
confidence: 99%
“…Remarkably, a few clinical trials have demonstrated the favorable effects of low‐molecular‐weight heparin (LMWH) on human tumors 17. LMWH inhibits the adhesion between platelets and tumor cells by hindering P‐selectin on activated platelets,17, 18, 19, 20 thus inhibiting the final stage of the metastatic cascade. Moreover, d ‐α‐tocopheryl succinate (TOS), the most effective form of vitamin E analogues, can inhibit the drug resistance of tumors and increase the apoptosis of various types of cancer cells,21, 22, 23 including B16F10 melanoma cells 24.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of evidence that P-selectin and L-selectin facilitate metastasis of tumour cells when they are still in the circulation [4,6]. Therefore, we aimed to differentiate between the contribution of tumour cell-derived VLA-4 and selectin ligands to metastasis of B16F10 melanoma.…”
Section: Differentiation Between P-selectin and Vla-4-mediated Melanomentioning
confidence: 99%
“…In the early phase of hematogenous metastasis P-selectin expressed on activated platelets and endothelium contributes to platelet-rich tumour cell emboli formation resulting in protection of tumour cells from innate immune system [4,5]. Lselectin expressed by leukocytes facilitates the interaction of the tumour microemboli with the endothelium [6,7].…”
Section: Introductionmentioning
confidence: 99%